Labour Markets and Job Creation in the GCC Countries - De Beuckelaerová, Karolien (2022)
This bachelor’s thesis examines the labor markets in the Gulf Cooperation Council (GCC), which comprises six states – Bahrain, Kuwait, Oman, Qatar, the Kingdom of Saudi Arabia, and the United Arab Emirates. Their labor markets are unique in many aspects, however, not in a good way. The main focus is placed on the issue of national unemployment and job creation. Major factors contributing to the unemployment of GCC citizens are discussed, revealing other challenges the GCC labor markets are currently facing underway. The thesis is divided into three chapters. The first one introduces the situation in the GCC labor markets. The second chapter deals with workforce nationalization policies through which the GCC governments have tried to increase national employment. The last chapter discusses an alternative channel through which jobs can be created, namely labor productivity growth and economic diversification.